Blowing up the fashion bubble, or nine things wrong with fashion: an outsider’s comment. A critical essay on fashion as a creative industry - Stankevičiūtė, Kristina (Creativity Studies, 2021)
The world of fashion has lived in a bubble long before the concept found its way into social networks. Well before the social networks themselves, in fact. The very emergence of fashion as an idea occurred within the bubble of the social life at Palace of Versailles, France, where the notorious Louis XIV sported great interest in the looks of his court in addition to those of his own. The article is an outsider’s attempt to have a sober look at the fashion industry that until recently seemed to have maintained the “structure of feeling” of the 17th century Palace of Versailles. Today’s social realities, however, put fashion in the state of a shock that probably equals that of the Storming of the Bastille in 1789, even though it is presumably much less sudden. Written in the manner of the most popular contemporary fashion media format – a bullet list, the text presents a conceptual analysis of the world’s second most wasteful yet poisonously attractive industry, critically reflecting on such characteristic values of the fashion field as concept and features, hierarchy, arrogance, resources and philosophy.